Science experiments you can eat - Cobb, Vicki, 1938- (Harper Trophy, 1994)
"Experiments with food demonstrate various scientific principles and produce an eatable result. Includes fruit drinks, grape jelly, muffins, chop suey, yogurt, and junket."--Resumé vydavatele